Pengaruh kompetensi auditor dan beban kerja Terhadap kemampuan auditor dalam mendeteksi Kecurangan Dengan skeptisme profesional Sebagai Variabel Intervening Studi Empiris Pada Kantor Akuntan Publik Di Kota Bandung - Ramadhan, Eka Falah; Yuniarti, Rita (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2026)
This study aims to determine whether workload and auditor competence both partially and simultaneously influence the auditor's ability to detect fraud through professional skepticism among external auditors working at Public Accounting Firms (KAP) in Bandung. The factors examined in this study include workload and competence as independent variables, professional skepticism as the intervening variable, and the auditor's ability to detect fraud as the dependent variable.The population for this study consists of all auditors at KAPs operating in Bandung; however, only 26 firms agreed to participate. While questionnaires were distributed to all active auditors, only 185 were fully completed and eligible for use. The sampling technique employed was non-probability sampling using the accidental sampling method. Data analysis was performed via multiple linear regression using SPSS 27.The results indicate that auditors with a high workload tend to experience a decrease in professional skepticism, which subsequently leads to a decline in their ability to detect fraud. Conversely, auditors with high competence tend to possess high professional skepticism, where such skepticism increases their level of awareness when encountering symptoms of fraud.